An Innovative Approach to Sustainability - Okan Pala (Journal of Sustainability Perspectives, 2021)
Solutions to sustainable development (SD) challenges are complex and context-specific. Ozyegin University (OzU) created a structure to manage all its sustainability endeavours aligned with these two facts. To this end, OzU first understood the priorities of Turkey to achieve SD in terms of SDGs.  Subsequently, the university conducted a self-assessment to determine the SDGs that it is most competent at.  By combining these two analyses, OzU determined the areas in which it can have the highest impact in the SD of Turkey. In conducting these analyses, a holistic approach was adopted, to consider the interconnectedness of the SDGs. The tools of the network analysis were employed to address the intertwined relationships among the SDGs. The analysis revealed four domains which led to the creation of four Sustainability Clusters. The clusters are positioned under the newly established Sustainability Platform managing and combining all the sustainability endeavors in relation with both these domains and otherwise. In this paper, the creation of processes of Sustainability Platform and Sustainability Clusters the structures which aim to contribute to the SD of Turkey will be elaborated.  Practical insights will be developed based on this structure